Ge 4s2 lone pairs and band alignments in GeS and GeSe for photovoltaics. Issue 39 (28th September 2021) - Smiles, Matthew J.; Skelton, Jonathan M.; Shiel, Huw; Jones, Leanne A. H.; Swallow, Jack E. N.; Edwards, Holly J.; Murgatroyd, Philip A. E.; Featherstone, Thomas J.; Thakur, Pardeep K.; Lee, Tien-Lin; Dhanak, Vinod R.; Veal, Tim D.
Abstract : GeS and GeSe with Ge 4s 2 lone pairs shown in the structure and observed at the top of the valence band using hard and soft X-ray photoelectron spectroscopy combined with density functional theory. Abstract : Germanium sulfide and germanium selenide bulk crystals were prepared using a melt growth technique. X-ray photoemission spectroscopy (XPS) was used to determine ionisation potentials of 5.74 and 5.48 eV for GeS and GeSe respectively. These values were used with the previously-measured band gaps to establish the natural band alignments with potential window layers for solar cells and to identify CdS and TiO2 as sensible choices. The ionisation potential of GeS is found to be smaller than in comparable materials. Using XPS and hard X-ray photoemission (HAXPES) measurements in conjunction with density-functional theory calculations, we demonstrate that stereochemically active Ge 4s lone pairs are present at the valence-band maxima. Our work thus provides direct evidence for active lone pairs in GeS and GeSe, with important implications for the applications of these and related materials such as Ge-based perovskites.